2018
DOI: 10.7717/peerj.4695
|View full text |Cite
|
Sign up to set email alerts
|

From Chilean Patagonia to Galapagos, Ecuador: novel insights on blue whale migratory pathways along the Eastern South Pacific

Abstract: BackgroundThe most traditional scheme for migration among baleen whales comprises yearly migrations between productive waters at high latitude summer feeding grounds and warmer waters at lower latitudes where whales calve and mate, but rarely feed. Evidence indicates, however, that large departures from this scheme exist among populations and individuals. Furthermore, for some populations there is virtually no information on migratory pathways and destinations. Such is the case of Chilean blue whales throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 61 publications
3
49
1
Order By: Relevance
“…The deployment of satellite telemetry devices has provided critical information on the distribution, migration and seasonal movements of many species of large whales [28][29][36][37][38][39][40]. Such information is required to assess and manage potential impacts of anthropogenic activities on highly migratory species and to identify potential drivers that may be hindering recovery [10].…”
Section: Introductionmentioning
confidence: 99%
“…The deployment of satellite telemetry devices has provided critical information on the distribution, migration and seasonal movements of many species of large whales [28][29][36][37][38][39][40]. Such information is required to assess and manage potential impacts of anthropogenic activities on highly migratory species and to identify potential drivers that may be hindering recovery [10].…”
Section: Introductionmentioning
confidence: 99%
“…Blue whale populations in the Southern Hemisphere were depleted by commercial whaling (IWC (International Whaling Commission) 2006) and their numbers have yet to recover (Branch et al 2004;Branch et al 2007). Furthermore, the species tends to inhabit deep offshore waters during the breeding season (Double et al 2014;Torres-Florez et al 2015;Lesage et al 2017;Hucke-Gaete et al 2018) and the limited cetacean-oriented survey efforts in deep waters of the western South Atlantic (e.g. Di Tullio et al 2016) translates in few chances of blue whale encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hundreds of blue whales have been observed off the coasts of Chile, Peru, and Ecuador during the austral summer when Antarctic and pygmy blue whales are mainly located farther south in or near the Southern Ocean off Antarctica (Williams et al 2011, Galletti Vernazzani et al 2017, which suggests that this area is occupied by another blue whale population with a unique distribution. This distribution may include the southern portion of the eastern tropical Pacific (ETP), as Chilean blue whales migrate from the Gulfo Corcovado to the Galapagos Archipelago during the austral winter (Hucke-Gaete et al 2018, Torres-Florez et al 2015. Using body length measurements collected by whaling operations, Branch et al (2007) found sexually mature Chilean blue whales to be intermediate in size between pygmy and Antarctic blue whales.…”
Section: Introductionmentioning
confidence: 99%